Competing in the age of AI : strategy and leadership when algorithms and networks run the world - Iansiti, Marco, 1961-; Lakhani, Karim R. (Boston, MA : Harvard Business Review Press, 2020)
"In industry after industry, data, analytics, and AI-driven processes are transforming the nature of work. While we often still treat AI as the domain of a specific skill, business function, or sector, we have entered a new era in which AI is challenging the very concept of the firm. AI-centric organizations exhibit a new operating architecture, redefining how they create, capture, share, and deliver value. Marco Iansiti and Karim R. Lakhani show how reinventing the firm around data, analytics, and AI removes traditional constraints on scale, scope, and learning that have constrained business growth for hundreds of years. From Airbnb to Ant Financial, Microsoft to Amazon, research shows how AI-driven processes are vastly more scalable than traditional processes, drive massive scope increase, enabling companies to straddle industry boundaries, and enable powerful opportunities for learning--to drive ever more accurate, complex, and sophisticated predictions. When traditional operating constraints are removed, strategy becomes a whole new game, one whose rules and likely outcomes this book will make clear. Iansiti and Lakhani: Present a framework for rethinking business and operating models Explain how "collisions" between AI-driven/digital and traditional/analog firms are reshaping competition and altering the structure of our economy Show how these collisions force traditional companies to change their operating models to drive scale, scope, and learning Explain the risks involved in operating model transformation and how to overcome them Describe the new challenges and responsibilities for the leaders of these firms Packed with examples--including the most powerful and innovative global, AI-driven competitors--and based on research in hundreds of firms across many sectors, this is the essential guide for rethinking how your firm competes and operates in the era of AI"--
The age of AI: artificial intelligence is transforming the way firms function and restructuring the economy -- Rethinking the firm: how software, networks, and AI are changing the fundamental nature of companies-the way they operate and compete -- The AI factory: the core of the new firm is a scalable decision factory, powered by software, data, and algorithms -- Rearchitecting the firm: to use the full power of digital networks and AI, firms need a fundamentally different operating architecture -- Becoming an AI company: how to transform and rearchitect the firm to leverage the power of data, networks, and artificial intelligence -- Strategy for a new age: digital firms enable and require a new approach to strategy -- Strategic collisions: what happens when digital firms compete ("collide") with traditional firms -- The ethics of digital scale, scope and learning: the ethical challenges generated by the transformation of the nature of firms -- The new meta: how the age of AI is changing the "rules of the game," with fundamental implications for all of us -- A leadership mandate: the age of AI is defining a new set of challenges for leaders of digital firms, traditional organizations, startups, regulatory institution, and communities.
Includes index.
HB
Keywords: Artificial intelligence -- Industrial applications; Competition; Leadership; Business planning